Outcomes of Intraplaque Verapamil Injection for Treatment of Peyronie’s Disease - Khalid Hussain, Bilal Ahmed, Maria Tariq, Azeem Ahmed, Bilal Akhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the outcomes of intraplaque verapamil injection for treatment of Peyronie’s disease. Aim:The purpose of this study is to evaluate the outcomes & efficacy of intraplaque verapamil injection in Peyronie’s disease management. Methods: The quasi experimental study was conducted from July 2018 to July 2019 on a group of 26 subjects suffering from Peyronie’s disease. After detailed history, complete physical and genital examination, the diagnosis was confirmed. After informed consent, questionnaires regarding pain and sexual satisfaction of patients were filled. All patients received verapamil injections on weekly basis for a period of 10 weeks. After that, all necessary variables were recorded and data analyzed using SPSS version 16. Results: Most of the patients in our study were in the age group of 30-65 years. 26.9 % patients were in the range of 51-55 years old. 53.8% patients got no effect of intralesional injection of verapamil on pain while pain relieved in 38.5% of patients & 7.7% patients experienced an increased in pain intensity after 10 weeks of intralesional injection of verapamil. 61.5%of patients satisfied with their sexual life after 10 week of injections & 30.8% of patients remained unsatisfied with their sexual life while in 7.7%of patients symptoms aggravated. 53.8% of patients experienced no change in size of lesion and curvature of penis, while 30.8% got less than 50% reduction in size of lesion while 15.4% of patients got more than 50% reduction in size after 10 weeks. Practical implication: We can easily find the efficacy of Verapamil injection for management of Peyronie’s disease Conclusion: This study concluded the efficacy of Verapamil injection for management of Peyronie’s disease disease causes significant decrease in size of lesion and improvement in sexual activity. Keywords: Peyronie’s disease